Sarcoidosis associated with infliximab therapy in ulcerative colitis: A case report. Issue 10 (March 2017) - Gîlcă, Georgiana-Emmanuela; Diaconescu, Smaranda; Bălan, Gheorghe Gh.; Timofte, Oana; Ştefănescu, Gabriela
Abstract: Rationale: Although immunomodulatory therapy has been clearly stated as an important landmark in treatment of ulcerative colitis, significantly improving the quality of life for patients with inflammatory bowel disease, there are several aspects to be considered regarding the possible side-effects of anti-TNF alpha agents. In spite of a good safety profile, biologic TNF antagonists may induce paradoxical inflammation, which can manifest as sarcoid-like granulomatosis, consisting of noncaseating granulomas in the affected organs. Patient concerns: We report the case of a 30-year-old male patient, with no personal or familial history of lung disease, with a personal history of ulcerative colitis (UC), under clinical remission following infliximab therapy in maintenance dose, who was admitted for treatment administration, but also for dyspnea, nocturnal sweating, and nonproductive cough. Diagnoses: Based on clinical manifestations, biological landmarks excluding various infections, CT scan, fibrobronchoscopy with bronchoalveolar lavage for culture and immunohistochemical examination, followed by mediastinoscopy with sampling of paratracheal lymph node, which underwent histopathological examination, the patient was diagnosed with drug- induced stage II pulmonary sarcoidosis. Interventions: Since the patient had developed severe allergic reaction after being administered Infliximab at admission, the biological treatment was immediately discontinued. Following the diagnosis of pulmonary sarcoidosis, corticotherapy was initiated. Patient outcomes: After corticotherapy was initiated, the patient had a favorable outcome at 3 months reevaluation, both regarding the course of ulcerative colitis and sarcoidosis. Lessons: Patients under biological therapy using anti-TNF alpha agents must be carefully monitored, in order to early identify potential paradoxical inflammation (such as sarcoidosis) as a side-effect. The drug-related pulmonary disease tends to improve upon withdrawal of the drug, with occasional requirement of steroid treatment. However, a thorough strategy should be assembled in the case of UC relapse in this patient category, with switching to adalimumab or surgical approach as main possibilities.